Adherence to treatment in patients with inflammatory bowel disease - K. A. Andreev; A. V. Gorbenko; Yu. P. Skirdenko; N. A. Nikolaev; M. A. Livzan; G. R. Bikbavova; M. M. Fedorin (Бюллетень сибирской медицины)
Inflammatory bowel disease (IBD) is a common pathology that reduces the quality and duration of a patient’s life. The cornerstone of treatment of IBD patients is polypharmacotherapy based on the use of salicylates, antibiotics, immunomodulatory and biological drugs, and topical dosage forms. Multicomponent treatment has shown to reduce the quality of life and negatively affect adherence to drug therapy in IBD patients.One of the leading causes of treatment failure is low treatment adherence, which leads to disease progression, disability, and increased financial costs. Currently, there are many factors that affect adherence to therapy, some of them are modifiable, which creates opportunities to improve the effectiveness of existing medical interventions. However, the available data on the level of adherence in IBD patients are not numerous and homogeneous, so a low level of adherence to drug therapy in IBD patients is registered in 7–72% of cases.An important issue in understanding adherence in IBD patients is a lack of research on the level of adherence to counselling and lifestyle modification. However, the course of IBD, treatment features related to the duration of therapy and necessary lifestyle modifications (nutrition), as well as regular monitoring of laboratory and instrumental parameters determine the need to assess adherence to lifestyle modification and counselling along with adherence to drug therapy.